Simulation and Quantitative Assessment of Sensor Placement in a Hydrogen Bus for Risk Mitigation - Xintao Deng; Jinwei Sun; Fuyuan Yang; Minggao Ouyang (Hydrogen)
The cleanliness of hydrogen energy throughout its life cycle has enabled its applications in transportation and buildings. However, such scenarios often involve the storage and use of hydrogen in enclosed spaces. Ensuring the facility’s safety during hydrogen accidental leakage through rapid detection and emergency measures has been a long-standing topic. In this work, we analyze hydrogen leakage in a hydrogen bus through CFD simulation. By extracting the hydrogen diffusion time and combining it with the leakage frequency and ignition probability, we quantitatively evaluate the placement of the sensors and propose an index for detection system assessment named the average detection delay index (ADDI). A near-field detection sensor was introduced to the system, which reduced the lower ADDI limit of the detection system by up to 10 times while reducing the system cost without changing the level of performance.